DEVELOPING ESP SYLLABUS AND TEACHING MATERIALS FOR PORT BUSINESS EMPLOYEES - Rizqiliyah Issabella (Widya Mandala Surabaya Catholic University, 2019)
This study is aimed to cater the needs of professionals of sea port business to enhance their English speaking proficiency. Due to their limited time to study, the design of the syllabus must focus on the materials they usually use in their daily operation. The syllabus and the materials were designed using ADDIE model which stands for Analyzing, Designing, Developing, Implementing and Evaluating. In the Analyzing stage, ten topics were needed in practicing their English. The program was designed for one term covering fifteen meetings for ninety minutes each. The syllabus and materials had been reviewed by the expert of the port business. The order of the materials presented was based on the scope, from the small to the broad ones. One material was tried out to a specific group of learners resembling the target group, and the learners showed positive remark on both of the materials and the delivery.